LEVEL OF TURMERIC ACID THERAPY EFFECTIVENESS TO REDUCE INTENSITY OF MENSTRUAL PAIN - Sri Mukhodim Faridah Hanum; lida khalimatus sadiyah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Menstrual pain is an incidence of discomfort during menstruation. The current incidence of menstrual pain in the world is very high. According to epidemiological studies, the incidence rate in the United States is estimated at 45-90%, while a menstrual pain in Indonesia is 64.25% of total women who have menstrual (Proverawati, 2012). It is necessary to handle both pharmacological and non-pharmacological therapies. Test the research to analyze the effectiveness level of non-pharmacology therapy (turmeric acid and green coconut water) for decreasing intensity of menstrual pain in adolescent at Faculty of Health Sciences Muhammadiyah University of Sidoarjo. The method of this research is experimental with the quantitative approach of pre and post-test of Wilcoxon.Summer sample 40 respondents. Data collection using questionnaires. The results of research using turmeric acid and green coconut water in pre and post-treatment there were significant changes after the 3rd-day treatments with P = 0,000 (p <0,05). To see the effectiveness of treatment with descriptive to know the mean value, got the result using turmeric acid with mean value 0,45 whereas green coconut water means value 0,60 with difference 0,15 point higher in green coconut water. Nodes in this study are the level of effectiveness of decreasing the intensity of menstrual pain better by consuming green coconut water than the use of turmeric acid,.suggested to increase understanding of the community will be important to use non-pharmacology therapy in overcoming menstrual pain.